Reinterpretasi Sejarah Lokal sebagai Sumber Pembelajaran Kontekstual: Tinjauan Historiografi dan Relevansinya dalam Pendidikan Modern - Renol Hasan; Ismaul Fitroh (CV Cendekia Paramartha, 2026)
This study examines the reinterpretation of local history as a source of contextual learning through a historiographical perspective in modern education. The research employs a non-empirical approach using a critical literature review of reputable academic sources related to historiography, pedagogy, and history education. The findings indicate a paradigm shift in historiography from descriptive narratives to reflective and contextual approaches that enable the integration of local experiences into learning processes. Local history demonstrates significant pedagogical relevance in enhancing historical consciousness, critical thinking skills, and the development of students’ cultural identity. Furthermore, the reinterpretation of local history contributes to conceptual transformation in history education by emphasizing constructivist, critical, and interdisciplinary approaches. This study highlights that local history functions not only as instructional content but also as an epistemological framework for meaningful and contextually relevant learning. The contribution lies in strengthening the integration between historiography and pedagogy within contemporary history education.